Health financing in Indonesia : (The World Bank, 2009)
In 2004 the Indonesian government made a commitment to provide its entire population with health insurance coverage through a mandatory public health insurance scheme. It has moved boldly already provides coverage to an estimated 76.4 million poor and near poor, funded through the public budget. Nevertheless, over half the population still lacks health insurance coverage, and the full fiscal impacts of the government s program for the poor have not been fully assessed or felt. In addition, significant deficiencies in the efficiency and equity of the current health system, unless addressed will exacerbate cost pressures and could preclude the effective implementation of universal coverage (UC) and the desired result of improvements in population health outcomes and financial protection. For Indonesia to achieve UC, systems performance must be improved and key policy choices with respect to the configuration of the health financing system must be made. Indonesia s health system performs well with respect to some health outcomes and financial protection, but there is potential for significant improvement. High-level political decisions are necessary on key elements of the health financing reform package.